2017
DOI: 10.1038/srep45178
|View full text |Cite
|
Sign up to set email alerts
|

Towards reproducible MRM based biomarker discovery using dried blood spots

Abstract: There is an increasing interest in the use of dried blood spot (DBS) sampling and multiple reaction monitoring in proteomics. Although several groups have explored the utility of DBS by focusing on protein detection, the reproducibility of the approach and whether it can be used for biomarker discovery in high throughput studies is yet to be determined. We assessed the reproducibility of multiplexed targeted protein measurements in DBS compared to serum. Eighty-two medium to high abundance proteins were monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…We have previously demonstrated that we can successfully detect and reproducibly monitor tens of proteins isolated from serum and DBS 4 samples using MRM, and here, we demonstrate that we can also do this in stored NBS samples collected between 1975 and 1985 (median CV 10.8%; Supplementary Fig. 2 ).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…We have previously demonstrated that we can successfully detect and reproducibly monitor tens of proteins isolated from serum and DBS 4 samples using MRM, and here, we demonstrate that we can also do this in stored NBS samples collected between 1975 and 1985 (median CV 10.8%; Supplementary Fig. 2 ).…”
Section: Discussionsupporting
confidence: 61%
“…As we have previously only processed DBS samples within 6 months of collection 4 , we had to determine whether we could detect the targeted protein peptides in stored NBS samples collected between 1975 and 1985 (Supplementary Table 1 ). We initially tested ten samples collected in 1975 and 1985, five from each year.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations